Expression of molecules associated with neuronal plasticity in the striatum after aspiration and thermocoagulatory lesions of the cerebral cortex in adult rats. - Szele, F; Alexander, C; Chesselet, M (1995)
Like the hippocampus, the striatum receives excitatory afferents from the cerebral cortex but, in the case of the striatum, very little is known about the molecular events associated with plasticity after lesions of this pathway. Using immunohistochemical techniques, we have examined the effects of cortical lesions induced either by aspiration of the frontoparietal cortex or by thermocoagulation of pial blood vessels on axonal and glial molecules associated with neuronal plasticity in the striatum. The growth associated protein GAP-43, a molecule present in axons and growth cones, decreased in the dorsolateral striatum after aspiration but not after thermocoagulatory lesions. In contrast, synaptophysin, a marker of synaptic vesicles, remained unchanged in the denervated striatum after both types of lesions. Immunostaining for basic fibroblast growth factor (bFGF) markedly decreased in striatal astrocytes after both lesions, despite an increased staining for glial fibrillary acidic protein (GFAP). The adhesion molecules tenascin, chondroitin sulfate proteoglycans, highly polysialylated neural cell adhesion molecule (PSA-NCAM), and laminin did not change significantly in the gray matter of the dorsolateral striatum after either type of lesion. These effects differed from those observed after partial denervation of the hippocampus and spinal cord, revealing marked regional differences in the response of axonal and glial proteins to afferent lesions. In addition, the results further indicate that cortical lesions have both similar and distinct consequences, depending on the procedure by which the lesions are induced, suggesting that cortical lesions associated with different types of pathology may differentially affect subcortical structures.